Toleration Group Governance in a Chinese Third Line Enterprise - Chen, Chao (New Perspectives on Chinese Politics and Society, 2018)
This book uncovers the mysterious social and political structures of China's "Third Front," the large state-sponsored development of inland China during the late Maoist period. This movement gave birth to a few important industrial bases such as Panzhihua and Liupanshui and had significant impact on megacities such as Lanzhou, Wuhan, and Chongqing. Yet, this is scarcely known to the West and even the younger generation of Chinese. Chen explores the ways that new industrial structures and hierarchies were created and operated, using political and sociological methodologies to understand what is distinctive in the history of the Chinese corporation. This book will be of immense interest to political scientists, sociologists, China scholars, and researchers of alternative economic structures. Chao Chen, with a PhD from the National University of Singapore, is a rising scholar based at Xiamen University's Institute of Taiwan Research. Specializing in state and society relations, comparative political economy, and qualitative methods, Chen is a name to watch. .